Active citizenship, education and service learning. (July 2013) - Birdwell, Jonathan; Scott, Ralph; Horley, Edward
This article explores how active citizenship can be encouraged through education and community action. It proposes that service learning and a renewed focus on voluntarism can both promote social cohesion between different ethnic and cultural groups while also fostering among the population a greater understanding of and commitment to civic culture. It reviews the international evidence on service programmes and the newly created National Citizen Service programme in the United Kingdom, arguing for a greater role for service learning in the citizen educational offer.